The effect of frequency presence of plastic surgery on social media - Ades, Andaleep Sadi (Edelweiss Applied Science and Technology, 2024)
Surgeons involved in plastic surgery may utilize social media avenues as a tool to reach out to their online audience and attract more potential consumers of their services. The purpose of this study is to explore the plastic surgery online presence with the main focus being on exploring the frequency of exposure to plastic surgery ads and the responses from the audiences. A quantitative cross-sectional design was adopted with the surveys distributed through TikTok and Snapchat being used to distribute the surveys to the targeted audience. A total of 850 participants were recruited for the study. The study findings showed that the exposure to plastic surgery ads was 100% with most of the participants encountering the ads more than ten times in a day. Also, most of the participants responded positively by clicking the ads, saving for later, seeking further information, or planning for plastic surgery. The study concluded that social media provides a good platform for plastic surgeons to market their products and reach more audiences. However, further research should be conducted to explore how companies and clinics should utilize social media channels to improve visibility and reach a wider audience.